Police deployment in armed conflict: a typology and multi-case application - Eck, Kristine (Policing and society, 2025)
Armed insurgency is one of the most extreme types of crisis that a state can face, but we know little about the role of the police in the context of domestic armed conflict. A cursory examination of the empirical record indicates that there is enormous variation in whether the police are tasked with counterinsurgency tasks; whether both the police and the military are deployed; and if so, whether it is the police or the military that lead the counterinsurgency effort. This manuscript introduces a conceptual framework of five different models of policing responses to insurgency: police vacuum, status quo policing, expanded policing, supportive policing, and counterinsurgency policing. The analytical traction of this framework is probed with three cases which saw varied police responses: the Malayan insurgency (1948-1960); the civil war in Nepal (1996-2006), and Myanmar (1948-present). The empirics show that the framework offers the flexibility to capture complex subnational and temporal variation in policing strategies. By developing meaningful and distinct categories of policing in conflict, this framework provides a tool to engage in deeper comparative work by mapping and measuring state responses to armed challengers. By centring the role of the police in armed conflict and probing empirical variation which has previously gone unstudied, the manuscript points to promising avenues for future research on policing, both inside and outside of armed conflict.